Sleeping Habits, Classroom Behaviour and Academic Performance of Senior High School Students - Toyong, Paul Junrey A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2020)
Being sleepy in class can have a vital impact on the academic perfor-mance of a student. Lack of sufficient and adequate sleep can be harmful and even deadly. It is a basic necessity of life and important part of learning. This study utilized descriptive and correlational de-sign to examine 119 senior high Electrical Installation and Mainte-nance (EIM) students who were selected through simple random sampling. Findings revealed that 88 percent of the students were sleep deprived and they usually sleep for less than 6 hours only. Two of the reasons of sleeping late were using of Facebook and Messenger account and playing mobile games. The third reason was making as-signments and homework. The most prevalent classroom behaviours were: students were sleepy during class discussions and they slept in class during vacant periods and the third prevalent behavior was they felt tired during classes. Sixty-one percent of the students have a gen-eral average of 75-79 which is only fairly satisfactory and 29 percent have 80-84 grade which is only satisfactory in the K-12 grading sys-tem. There was a significant negative relationship (cc= -0.420 and p=0.000) between number of hours of night sleep and sleepiness classroom behavior. This suggested that the less number of hours of night sleep is correlated to high occurrence of sleepiness classroom behavior. There was a significant positive relationship (cc=0.627 and p=0.000) between number of hours of night sleep and academic per-formance. This suggested that the high number of hours of night sleep is associated to high academic performance. On the other hand, stu-dents with less sleep had low academic performance. There was a sig-nificant negative relationship (cc= -0.544 and p=0.000) between sleepiness classroom behavior and the academic performance. This implied that high occurrence of sleepiness classroom behavior is as-sociated to low academic performance. The implications may serve as basis for policy makers, school administrators and teachers to ed-ucate students including the parents on the proper use of mobile phones and other gadgets. The parents need to set sleeping time or lights-off rules and regulate the use of mobile phones. Sleeping time or routine shall be imposed. School administrators and teachers need to craft a well-planned and well-designed policy on giving assign-ments and homework to attain high scholastic achievement.